2018
DOI: 10.1038/s41598-018-30509-3
|View full text |Cite
|
Sign up to set email alerts
|

Drug-based perturbation screen uncovers synergistic drug combinations in Burkitt lymphoma

Abstract: Burkitt lymphoma (BL) is a highly aggressive B-cell lymphoma associated with MYC translocation. Here, we describe drug response profiling of 42 blood cancer cell lines including 17 BL to 32 drugs targeting key cancer pathways and provide a systematic study of drug combinations in BL cell lines. Based on drug response, we identified cell line specific sensitivities, i.e. to venetoclax driven by BCL2 overexpression and partitioned subsets of BL driven by response to kinase inhibitors. In the combination screen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…1). In line with procedures applied by other drug screen labs 5,6,13,14 , we used viability as assessed by ATP content (CellTiter-Glo) as the main readout to gauge drug responses in 2D and 3D cultures. Additional readouts included measurement of confluency (2D), spheroid diameter (3D) and cell death (2D).…”
Section: Resultsmentioning
confidence: 99%
“…1). In line with procedures applied by other drug screen labs 5,6,13,14 , we used viability as assessed by ATP content (CellTiter-Glo) as the main readout to gauge drug responses in 2D and 3D cultures. Additional readouts included measurement of confluency (2D), spheroid diameter (3D) and cell death (2D).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the Raji cell line was resistant to the MB-3 inhibitor. Previous studies indicate that this cell line is drug insensitive, particularly to inhibitors of the PI3K and BCR pathways [51, 52]. Overall, GCN5 HAT inhibition disrupts BCR signaling and reduces phosphorylation of key effectors, thereby reducing viability and inducing apoptosis in Burkitt lymphoma cells.…”
Section: Discussionmentioning
confidence: 89%
“…Several papers also have reported that BET inhibitors synergize with cell cycle checkpoint modulators, such as CDK inhibitors or ATR inhibitors . Zhang et al .…”
Section: Discussionmentioning
confidence: 99%